LEGAL TRANSITION TO THE LEGISLATIVE FRAMEWORK FOR INVESTMENTS IN THE GREEN ECONOMY - PhD. Якубова Мадинабону Абдумаликовна (American Journals, 2023)
This article examines the potential of legal transfer of innovation policies and regulations to facilitate investments in the green economy. Five keywords: legal transfer, green investments, legislative framework, comparative law, transition to sustainable development. The introduction provides general information on the concept of a green economy and the need for large-scale green investments. The methodological section describes a doctrinal approach to legal research using a comparative analysis of the regulatory framework in different jurisdictions. The theoretical result is a comparative analysis of the legislative methods used to stimulate green investments and the identification of best practices for their legal transfer. The practical result is proposed legal reforms to ensure sustainable investment, including tax breaks, subsidies, public procurement standards, and mandatory green investment regulations for institutional investors. It concludes by summarizing the main findings and arguing for multi-level policy coordination and adaptive legal frameworks to stimulate the transition to sustainable development.
Keywords: Legal transfer, green investments, legislative framework, comparative law, transition to sustainable development.